ICT NETWORK AS THE BASIS OF COMPUTER-ORIENTED METHOD OF DEVELOPMENT OF FUTURE PHILOLOGISTS' PROFESSIONAL COMPETENCE - S. S. Protska (Borys Grinchenko Kyiv Metropolitan University, 2017)
The article determines the role of ICT network as the basis of computer-oriented methods of development of future philologists' professional competence; presents the ICT network typology, reflecting ICT-oriented education; outlines the essential characteristics of the term "computer-oriented methods of formation of future philologists' professional competence". All innovative changes primarily depend on the student, his creativity, willingness to lifelong learning, the need for professional growth, flexibility socio-pedagogical thinking, humanistic orientation of the individual. The research claims that the ICT network has become the most effective tool used in computer-based education. Under the term "computer-oriented methods of development of future philologists' professional competence" in our research we consider the set of components for computer-based education, in particular, Web services, that are aimed at involving all the students and teachers in educational activity in the Internet environment. The signs of computer-oriented methods of development of future philologists' professional competence are the completeness, the integrity and the interdependence of their components: the clear aim and purpouses, defined contents, forms, methods, tools and diagnostics results. The foregoing research makes it possible to carry out some theoretical conclusions. Taking into account the specificity of Bachelor-philologists' future careers, it is necessary to state that the role of ICT network as the basis of computer-oriented methods of future philologists' professional competences development is displayed in the interdependence of the components of computer-oriented methods of future philologists' professional competences development, the use the potential opportunities of the ICT networks as the basis of computer-oriented methods of future philologists' professional competences development, allows them to perform in the professional tasks to realize not only information and technological, but also psychological and pedagogical goals that will bring education to a new level of innovation and provide future philologists' personal development. The given results of this scientific exploration and the investigation of the ICT network typology, which present the ICT-based education, give us the opportunity to claim that they are support mechanisms to improve self-motivation of university students' independent educational activity.